Project for Water Supply to Saurashtra and Kachchh Region Draft Report - Planning Commission (Planning Commission, 1988)
The study on water supply challenges in the arid regions of Saurashtra and Kachchh examines strategies to meet drinking water and local demand amidst recurrent droughts, projected to persist until the Narmada Canal project completion in 2001. With an estimated population of 159.66 lakhs, the region’s water demand ranges from 775 million liters per day in scarcity years to 1,380 million liters in normal years, while local sources provide only 508 million liters per day. Proposed solutions include transferring Narmada waters via a multipurpose bridge, interlinking existing reservoirs, and enhancing groundwater use. Economic viability is addressed through tolls and water charges, and the establishment of an autonomous management body is recommended. The study underscores a combination of immediate interventions and long-term planning to ensure sustainable water supply for the region.
Government of India Planning Commission December 1988
Government of India Planning Commission December 1988
Keywords: Saurashtra; Kachchh; Water Supply; Narmada Canal; Drought Management; Groundwater Resources; Surface Water; Reservoir Interlinking; Water Demand; Multipurpose Bridge; Water Charges; Planning Commission